Procedure-specific Cardiac Surgeon Volume associated with Patient outcome following Valve Surgery, but not Isolated CABG Surgery - Ch'ng, S.; Cochrane, A.; Wolfe, R.; Reid, Christopher; Smith, C.; Smith, J. (Elsevier Australia, 2015)
Purpose: Trends towards surgical sub-specialisation to improve patient-outcomes are well-documented and largely supported by evidence. However few studies have examined whether this benefit exists within adult-cardiac surgery. To answer whether sub-specialisation within adult-cardiac surgery improves patient-outcomes, this study assessed the relationship between procedure-specific and total-cardiac surgeon-volume and mortality and morbidity in cardiac-valve and coronary artery bypass grafting (CABG) surgery. Methods: Data came from the Australian and New Zealand Society of Cardiac and Thoracic Surgeons (ANZSCTS) registry from 2001 to 2010 and included 23 hospitals, 109 surgeons, 20,619 patients with isolated-CABG-surgery and 11,536 patients with a valve-procedure. Hierarchical logistic regression using generalised estimating equations was used to analyse outcomes. Measures included operative-mortality and occurrence of a complication (deep sternal wound infection, new stroke, acute kidney injury). Results: Crude operative mortality (and complication rates) were 1.7% (4.9%) and 4% (11%) in the isolated-CABG and valve-surgical populations respectively. A greater procedure-specific surgeon volume was associated with reduced mortality and complication rates in valve-surgery but not isolated-CABG. There was a 33% decrease in odds of dying for every additional 50 valve procedures performed [OR 0.67, p=0.003]. Conversely, greater total-cardiac surgical volume for individual surgeons did not result in improved outcomes, for both isolated-CABG and valve populations. Conclusions: Our finding of an association between increased valve-specific surgeon volumes with improved valve-surgery outcomes, and absence of an association between these outcomes and annual total-cardiac surgical experience supports the case for sub-specialisation specifically within the field of valve surgery.